Views of secondary education teachers on the use of mixed reality - Marín-Díaz, Verónica; Sampedro-Requena, Begoña Esther (Frontiers in Education, 2023)
The advance of the so-called emergent technologies in the field of education goes hand in hand with the previous experiences and beliefs of teachers, or lack thereof, with and about them. Among all the digital resources available, Mixed Reality (MR) is currently awakening the interest of educators, given that it combines virtual and augmented reality. Although both of these technologies are already present in many mixed methodologies utilized for teaching and learning processes, this is not the case of MR. Thus, it is necessary to discover the perspectives of educators on the use of MR, to be able to forecast its successful implementation in classrooms. Thus, the present article shows data obtained from a study with 219 Secondary Education pre-service teachers in Spain. The data collected through a 31-item ad hoc questionnaire pointed to differences in the perception of Mixed Reality in the teaching process as a function of gender, with women considering that it will make the classroom methodology more communicative, also believing that it will promote the reading comprehension of the texts that are utilized in each school subject. Thus, we can conclude that mixed reality is defined as a tool that promotes the learning process of secondary school students